Does Simantri Matter In Economic Sustainability? A Study From Agricultural Sector In Bali, Indonesia - Desak Made Marysha Dewi; Ida Ayu Nyoman Saskara; Ni Putu Wiwin Setyari (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
The Integrated Agricultural System (Simantri) is one of the Bali Provincial Government’s flagship programs to increase the agricultural sector’s role in supporting Bali Mandara. Simantri encourages the sustainability of Bali’s economic life, which until now the majority of Balinese people still depend on agricultural sector. The purpose of this study is to provide analysis and determine the level of sustainability of the Simantri program and determine scenarios and formulate recommendations and strategies for the sustainability of Simantri program. The method used is to analyze using MULTIPOL. The result of the research is the level of sustainability of the Integrated Agricultural System (Simantri) in Tabanan Regency is effective because most of the people make a living as farmers. The strategy for Simantri suistainability by giving tool training socialization, group development activities, providing the assistance of capital, build the infrastructure rehabilitation, drafting and structuring related regulations, and optimizing companion roles